Hubungan Pengawasan Orang Tua Dalam Penggunaan Gadget Dengan Tingkat Perkembangan Pada Anak Usia Prasekolah di Wilayah RW 001 Kelurahan Pondok Betung Kecamatan Pondok Aren Kota Tangerang Selatan - Dinda Wardianti; Diana Rhismawati Djupri; Aat Yatnikasari; Nila Rostarina (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Gadgets are technologies that can access media. Parental supervision in the use of Gadgets by preschool children is an effort to monitor children's activities in using Gadgets, which can have positive or negative impacts on their development. Parental supervision is crucial for children's development. This study aims to determine the relationship between parental supervision in the use of Gadgets and the development of preschool children in RW 001, Pondok Betung Village, Pondok Aren Sub-district, South Tangerang City. This research employs a quantitative method with a cross-sectional approach. The population of this study consisted of 61 respondents, all of whom were included as the research sample (total sampling). The research instruments used were a questionnaire on parental supervision in the use of Gadgets and the KPSP. Data analysis was performed using univariate and bivariate analyses with the chi-square statistical test. The results showed a p-value of 0.0001 (p-value <0.05), indicating a significant relationship between parental supervision in the use of Gadgets and the development of preschool children. This highlights the importance of parental supervision in the use of Gadgets by preschool children.